تحليل تربوي لاستراتيجيات التعلم النشط ومعوقات توظيفها في مرحلة التعليم الأساسي: دراسة ميدانية (Comprehensive Journal of Science, 2026)
The study aims to identify the obstacles hindering the implementation of active learning strategies in basic education in Al-Marj city. A questionnaire was used as the main tool for data collection from a sample of 100 teachers, and the results were analyzed using the t-test and one-way ANOVA. Findings revealed statistically significant differences between the hypothetical and actual means across all four dimensions (school environment, students, curricula, and administration), confirming that these obstacles are real and substantial. The results also indicated no significant differences based on gender, specialization, or years of experience, while a significant difference was found in administrative obstacles among educational stages, with higher perceptions reported by teachers in the early years. The study concludes that classroom environment, curricula, and administrative support represent the most critical challenges, and recommends continuous teacher training, curriculum development, and the provision of supportive classroom and administrative environments to ensure the successful application of active learning.
Keywords: Active learning, Basic education, Curricula, School administration.